A broadband reflective-type half-wave plate employing optical feedbacks - Gaochao Zhou (Nature Portfolio, 2017)
Abstract We propose and demonstrate a type of a broadband half-wave plate that operates in the reflective mode. It consists of a metal grating embedded in a dielectric slab and placed on top of a grounded metal surface. We theoretically show that owing to the optical feedback effect which originates from the wave reflections at the air-dielectric interface, the proposed half-wave plate exhibits a broadened and flattened response when comparing to the case where the feedback effect is absent. Such a prediction is validated using both numerical and experimental works carried out on a half-wave plate designed at 10 GHz. Moreover, our theoretical analysis also reveals that the half-wave plate has an interesting feature of broad angular response. Taking advantage of these features, we experimentally demonstrate that the proposed device can function as a freely tunable linear polarization converter with polarization conversion residues less than −20 dB in a wide frequency band, under the condition that the incident angle is as large as 45 degrees.